19th century Venezuelan painting: The tragic in Cristobal Rojas' painting (Mayéutica Revista Científica de Humanidades y Artes, 2020)
In the 19th century, Venezuelan painting is determined and establishes new images that educate people between new and old beliefs, personified in the figure of the hero, where men are exalted through courage, sacrifice for patriotic ideals. These elements have already been used by artists of previous periods and, they announce precepts of a modernity that will be in charge of civilizing the Latin American man to equal itto the European man. This Latin American modernity is presented through the hero in the painting, as a symbol of independence, liberation, creating a new history from the painting, as evidenced in the representation of The Death of Athanasius Girardot in Barbara in 1883, made byChristopher Rojas, who uses the tragic as a historical fact from a poetic, romantic and moving.
Keywords: art history; 19th century art; Cristóbal Rojas; painting; tragedy